An Efficient Protection-Free One-Pot Chemical Synthesis of Modified Nucleoside-5′-Triphosphates. (2nd July 2016) - Shanmugasundaram, Muthian; Senthilvelan, Annamalai; Xiao, Zejun; Kore, Anilkumar R.
ABSTRACT: A simple, reliable, and an efficient "one-pot, three step" chemical method for the synthesis of modified nucleoside triphosphates such as 5-methylcytidine-5′-triphosphate (5-MeCTP), pseudouridine-5′-triphosphate (pseudoUTP) and N 1 -methylpseudouridine-5′-triphosphate (N 1 -methylpseudoUTP) starting from the corresponding nucleoside is described. The overall reaction involves the monophosphorylation of nucleoside, followed by the reaction with pyrophosphate and subsequent hydrolysis of the cyclic intermediate to furnish the corresponding NTP in moderate yields with high purity (>99.5%).